Property Market Research (SGP 3113)- Quiz I - Mar Iman, Abdul Hamid (2007)
Contains MS Word's (Word 97-2003) materials: Property Market Research's Quiz I. Contents are based on Chapter 1 - Introduction and Chapter 2 - Fundamental Elements of Market Research.